Pengaruh Budaya Organisasi dan Kompetensi Terhadap Kinerja Pegawai Kantor Kelurahan Daya Kota Makassar - Nur Alam A; A Rum Tajang; Ansar Taufik (STIM-LPI Makassar, 2022)
This study aims to analyze the influence of Organizational Culture and Competence on employee performance at the Daya Village Office, Makassar City This research was conducted at the Daya Kelurahan Office, Makassar City, with a population and sample of all employees, totaling 81 people. Data was collected by distributing questionnaires and documentation. Data were analyzed through Validity Test, Reliability, Multiple Linear Regression Analysis, and Coefficient of Determination (R2), using the SPSS application. The results showed that Organizational Culture and Competence had a positive and significant effect on employee performance. The dominant organizational culture variable influences the performance of employees at the Daya Makassar Village Office